Orthodontic repositioning of a malposed and dilacerated central incisor - Hegde, C; Hegde, M; Parajuli, U (Kathmandu University Medical Journal, 2010)
Dilacerated teeth are commonly seen in the maxillary anterior region. They are a cause for concern to both patients as well as parents when such teeth do not erupt or erupt in an unusual position. Careful planning is required while aligning such teeth. Orthodontists often hesitate aligning severely dilacerated teeth due to high chances of failure. A case of a dilacerated and malposed right central incisor in an eleven-year-old male patient is presented here. The tooth was orthodontically repositioned despite its unusual position and severely dilacerated root. Key words: Dilacerated teeth; Malposed teeth; Dilacerated central incisor. DOI: 10.3126/kumj.v7i4.2771 Kathmandu University Medical Journal (2009) Vol.7, No.4 Issue 28, 435-437